Diamond Supercapacitors: Towards Durable, Safe, and Biocompatible Aqueous-Based Energy Storage - Chambers, Andre; Prawer, Steven; Ahnood, Arman; Zhan, Hualin (Frontiers in Chemistry, 2022)
Durable and safe energy storage is required for the next generation of miniature bioelectronic devices, in which aqueous electrolytes are preferred due to the advantages in safety, low cost, and high conductivity. While rechargeable aqueous batteries are among the primary choices with relatively low power requirements, their lifetime is generally limited to a few thousand charging/discharging cycles as the electrode material can degrade due to electrochemical reactions. Electrical double layer capacitors (EDLCs) possess increased cycling stability and power density, although with as-yet lower energy density, due to quick electrical adsorption and desorption of ions without involving chemical reactions. However, in aqueous solution, chemical reactions which cause electrode degradation and produce hazardous species can occur when the voltage is increased beyond its operation window to improve the energy density. Diamond is a durable and biocompatible electrode material for supercapacitors, while at the same providing a larger voltage window in biological environments. For applications requiring higher energy density, diamond-based pseudocapacitors (PCs) have also been developed, which combine EDLCs with fast electrochemical reactions. Here we inspect the properties of diamond-related materials and discuss their advantages and disadvantages when used as EDLC and PC materials. We argue that further optimization of the diamond surface chemistry and morphology, guided by computational modelling of the interface, can lead to supercapacitors with enhanced performance. We envisage that such diamond-based supercapacitors could be used in a wide range of applications and in particular those requiring high performance in biomedical applications.